VARIATIONS IN ISOTOPIC AND TRACE-ELEMENT COMPOSITION OF LAVAS FROM VOLCANOES OF THE NORTHERN GROUP, KAMCHATKA, IN RELATION TO SPECIFIC FEATURES OF SUBDUCTION - Volynets O.N.; Babanskii A.D.; Gol'tsman Yu.V. (My University, 2000)
Two associations were revealed among the Northern group volcanoes in Kamchatka by study of chemical and isotopic composition of their lavas. The first association includes volcanoes located north of the Kamchatka River, e.g., Shiveluch, Zarechnyi, Kharchinskii volcanoes, and Kharchinskii regional zone of cinder cones. The second association comprises volcanoes located south of this river, e.g., Klyuchevskoi, Ploskie Sopki, Tolbachik, Nikolka volcanoes, as well as Tolbachik and Ploskie Sopki regional zones of cinder cones. The volcanic rocks of the first association differ from those of the second one in higher magnesium contents; elevated Sr; lower Ca, Sc, Y, and Yb; higher Sr/Y, K/Ti, La/Yb, Zr/Y, Th/Yb, Ni/Sc, Cr/Sc and lower Ca/Sr and U/Th ratios. Variations of Sr and Nd isotopic ratios in volcanics of these associations overlap. The covariations between Sr and Nd isotope characteristics and isotopic ratios with some major- and trace-element contents differ in these two associations. We concluded that the parental melts for the rocks of these associations were formed during the metasomatic transformation of mantle wedge under the influence of two different agents: partial melts generated within the subducted slab, for the northern volcanoes; and fluids derived from the subducted slab, for the southern ones. This discrepancy is probably related to different subduction conditions: oblique, gently dipping, slow subduction (like in the western Aleutians) beneath the northern volcanoes; and orthogonal subduction of ancient oceanic crust beneath the southern ones.